KELUARGA DAN PROBLEMATIKANYA MENUJU KELUARGA SAKINAH (Tinjauan dalam Persfektif Marrital Psikologi) - N. Kardinah (Psympathic : Jurnal Ilmiah Psikologi, 2009)
This journal was made to describe a real condition of family’s affair and all aspects within family life, how to solve family business and discussing hints and strategies to create a sakinah’s family (harmonic family). Adults—in this article—were the subject and are seen as individuals that prepare themselves to step onto marriage life—which would then all fundamental aspects of marriage life and family business must be learned by adults so they can manage their family and marriage life.An ideal family was built upon consensus of vision and basis of knowledge and not just following emotional pressure and lust. Everything has its own way, either in techniques and strategies to implement all ideal theories in real life. A family which has clear vision and orientation of how to solve all family business can make an ideal roadmap regarding family education for its member; they would also can preserve and teach a meaningful moral values, social, tradition and religious values accordingly.